Protein hunger of the feed sector: the alternatives offered by the plant world. Issue 1 (14th December 2020) - Parisi, Giuliana; Tulli, Francesca; Fortina, Riccardo; Marino, Rosaria; Bani, Paolo; Dalle Zotte, Antonella; De Angelis, Anna; Piccolo, Giovanni; Pinotti, Luciano; Schiavone, Achille; Terova, Genciana; Prandini, Aldo; et al.
Abstract: The expected future demand for highly nutrient animal food products will push the animal production system to search for new sources of high-quality protein feedstuffs. In this scenario, economic and environmental issues will have to be considered while reducing the competition with the plant-based human food chains. Legume grains and some oilseed cakes, by-products from the oil industry, are the main protein sources for ruminants and terrestrial monogastrics such as pigs and poultry. Their relevant role will hold in the next decades, but it is necessary to increase the diversification of sources that can be grown profitably throughout the world, including European countries. Microalgae are a promising source of protein and other nutrients for animal feeding. However, an amazing richness of biologically active substances makes these organisms very interesting as feed ingredients, as their role go far beyond the supply of nutrients. Due to the limited usage of microalgae as human foodstuffs or food ingredients, low competition between microalgae-based feed and food chains is predictable. This review aims to synthesise current knowledge on minor pulses and other protein-rich plant products and microalgae, as alternative ingredients to the conventional animal protein sources, focussing on their production, availability, and nutritional values. Points of strength, weakness, opportunity and threat related to the use of these protein sources in animal feeding are separately analysed through a SWOT approach to underlie future needs in terms of research and/or technological development that could help valorise these nutrient sources as feed ingredients.